The Impacts of Stakeholder Pressure, Profitability, and Audit Committee on the Quality of Sustainability Reports - Baroroh, Niswah; Yanto, Heri; Pertiwi, Meilani Intan; Ningrum, Meldica Widya; Luthfi, Muhammad Fikri (Universitas Pendidikan Indonesia, 2025)
This study aims to examine the influence of employee and consumer pressure on the quality of sustainability reports, with the audit committee as a moderating variable. Using panel data regression and Moderated Regression Analysis (MRA), this research analyzes secondary data from LQ45-listed companies in Indonesia from 2019 to 2022. The findings indicate that employee and consumer pressure positively affect sustainability report quality, reinforcing the importance of stakeholder expectations in corporate transparency. However, profitability does not significantly impact sustainability report quality, suggesting that financial performance alone does not determine sustainability disclosure practices. The audit committee weakens the effect of employee pressure on sustainability reporting, indicating its role in prioritizing regulatory compliance over internal stakeholder demands. Meanwhile, the audit committee does not moderate the impact of consumer pressure or profitability, highlighting its limited role in addressing external sustainability concerns. Theoretically, these findings support stakeholder theory by demonstrating how non-financial pressures influence corporate sustainability practices. In practice, companies should recognize sustainability reporting as a strategic tool for fostering stakeholder trust and improving corporate reputation rather than merely a regulatory obligation. Policymakers and regulators should also consider strengthening governance mechanisms to enhance corporate sustainability disclosures. The novelty of this study lies in its investigation of the audit committee’s moderating role in stakeholder-driven sustainability reporting, providing new insights into corporate governance and sustainability dynamics.